Compreendendo a realidade noética no hermetismo antigo: uma proposta de interpretação reflexiva sobre o noûs no Corpus Hermeticum - Vieira, Thiago Barbosa (2022)
This work intends to collaborate with the understanding of the notion of noûs in the Corpus Hermeticum. The Hermetica is considered a genre of texts whose authorship is attributed to Hermes Trismegistus or to equally mythical figures associated with this character. The Corpus Hermeticum is a collection known for being part of the philosophical/theoretical Hermetica. Scholars believe that the texts in this corpus were, for the most part, written between the 2nd and 3rd centuries CE in the historical-geographical context of Hellenistic and Roman Egypt. The modern editions of the Corpus Hermeticum contain seventeen treatises with philosophical-theological content. Noûs (νοῦς) is a word of Greek origin and is usually translated as “mind”, “intellect”, “intelligence”, etc. In the context of hermeticism, noûs establishes a strong point of support in the whole hermetic soteriological proposal and, consequently, in its paideia, in which the adept of hermeticism is guided to experience a process of recognition and recovery of the divine nature of the human being through a eusébeia and the awakening of its noûs to a “true” reality, inapparent. The objective is to clarify the philosophical and religious meanings of the concept of noûs in the Corpus Hermeticum by carrying out a study on the term, taking into account the cultural and historical context of its production, relating possible Greek philosophical and Egyptian cultural influences. In this way, the proposal of reflective interpretation is constructed considering the authenticity of the hermetic discourse beyond its previous influences and focusing on its understanding of the noûs.